Expectations about fertility and field of study among adolescents: A case of self-selection? - Micha G. Keijer; Aart C. Liefbroer; Ineke Nagel (Comparative Population Studies (CPoS), 2019)
In recent studies on the association between education and fertility, increased attention has been paid to the field of study. Women who studied in traditionally more "feminine" fields, like care, teaching, and health, were found to have their children earlier and to have more children than other women. A point of debate in this literature is on the causal direction of this relationship. Does the field of study change the attitudes towards family formation, or do young adults with stronger family-life attitudes self-select into educational fields that emphasize care, teaching, and health? Or do both field of study preferences and family-life attitudes arise before actual choices in these domains are made? We contribute to this debate by examining the relationship between fertility expectations and expected fields of study and occupation among 14-17 year-old adolescents. We use data collected in 2005 from 1500 Dutch adolescents and Structural Equation Modelling (SEM) to examine the associations between expected field of study and occupation and fertility expectations. Our results show that expectations concerning fertility and field of study are already interrelated during secondary education. Both female and male adolescents who expect to pursue studies in fields that focus on care and social interaction (like health care, teaching etc.) are less likely to expect to remain childless. This holds equally for girls and boys. In addition, girls who more strongly aspire to an occupation in which communication skills are important also expect to have more children. We did not find any relationship between expectations of pursuing a communicative field of study and occupation and expectations of earlier parenthood. In addition, among boys, we find that the greater their expectation of opting for an economics, a technical, or a communicative field of study, the less likely they were to expect to remain childless. Boys who expected to study in the economic field also expect to have their first child earlier, but boys expecting to pursue a technical course of studies expect to enter parenthood later. We also found that those who expect to pursue cultural studies are more likely to have a preference for no children, or if they do want children, to have them later in life. Overall, our findings suggest that the processes of elective affinity between the communicative fields of study and work on the one hand and fertility on the other hand are more or less comparable for boys and girls. With respect to the other domains, we find, apart from the gender differences in the relation between fields of study and childlessness, hardly or no gender differences in the expected timing of parenthood and the number of children. The genders do differ in their level of preference for communicative and economics-related fields of study and occupation, but if they do have the same preference, the association with fertility expectations is more or less similar.
urn:nbn:de:bib-cpos-2019-11en2
Keywords: 300; Education; Fertility; Field of study; Adolescent expectations